Age and type of instruction (CLIC vs. traditional EFL) in lexical development - Agustín-Llach, Maria Pilar (International Journal of English Studies, 2016)
The present paper compares the vocabulary development of a group of CLIL and of traditional EFL learners along three years. The observation that a CLIL approach might provide with larger benefits in the long run vocabulary is the starting point of this study. We had learners in the two groups complete a letter writing task. These writings were then scrutinized for L1 influence in the form of borrowings and lexical creations. The frequency of the words in the letters was also object of analysis. Results revealed that CLIL learners perform slightly better but non-significantly better than traditional EFL along the three years. Furthermore, the evolution of L1 influence and word use also followed an expected improvement pattern as learners went up grade. However, our results do not provide evidence of a growing CLIL advantage with increasing experience. The young age and low proficiency of learners in the present study might be blocking this possible advantage found elsewhere.